The craft & art of bamboo 30 eco-friendly projects to make for home & garden - Stangler, Carol 1946- (Lark Books, 2008)
Beautiful, sustainable bamboo is one of the most popular materials around for gardens and home de?cor, the "it" plant of the green movement. This highly regarded introduction to the material, revised and updated, offers rich history, fascinating background and great projects, and illustrates how to contain bamboo in the landscape. It covers all the tools and techniques you need for harvesting, storing, and making things with bamboo. Thirty how-to projects include bamboo fences, trellises, chopsticks, teacups, and even an outdoor shower.